Transhuman Perspective of Machine’s (Artificial Intelligence) Identity in Brown’s Origin: A Discourse Analysis - Shahwar, Dur e; Imtiaz, Akifa; Azam, Mian Khurram Shahzad (Journal of Development and Social Sciences, 2024)
This paper aims to analyse the construction of machine identity in Brown’s Origin through artificial intelligence (AI) character Winston. Using Gee’s discourse analysis, this research maps out how Winston enacts his identity beyond the machine roles of an assistant, in terms of language, interaction and narrative structure to human-like characteristics such as empathy, agency and creativity. The analysis is also accompanied by Bostrom’s transhuman philosophy, which questions the ethics of integrating AI into human society, its free will and decision making. Explicating the specific tendencies of Winston’s linguistic structure and narrative, the paper uncovered that AI’s identity presents arguments of transhumanism that are self-representing facets of superintelligence, ethical alignment and existential risks of AI technologies. Finally, this study advances the conversation about AI and transhumanism, and how narrative’s text is reframing what it means to be human or otherwise, an agent, and a subject in conjunction with machines. This study invites scholars to explore transhuman perspectives in performing AI in real life scenarios for productive use of AI.